Decline of the Vlach settlement in the Pindos region in the period of socio-political changes in Ottoman Turkey (18th-29th century) - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2021)
The aim of the paper is to present the conditions of a significant outflow of Vlachs from the Pindos region, which is commonly treated as one of traditional areas of the Vlachs’ settlement. The migrations lasted several decades, the majority of migrants stayed on the Turkish territory, although some families migrated to other countries, especially to the central-eastern Europe. The population movements were caused by worsening security and living conditions, connected with activity of bandits and political-military turbulence in the European part of the Ottoman Turkey. First, tradesmen and craftsmen migrated, then the shepherds started looking for new pastures and locations for their settlement. As a result, the Wallachian settlers dispersed through upland-mountainous regions of Thessaly, Thrace, Macedonia, Bosnia. They settled in towns in Austria, Serbia, Greece, Bulgaria or Romania.